Physical activity: the key to life satisfaction - correlations between physical activity, sedentary lifestyle, and life satisfaction among young adults before and after the COVID-19 pandemic - Bácsné Bába, Éva; Lengyel, Attila; Pfau, Christa; Müller, Anetta; Bartha, Éva Judit; Balogh, Renátó; Szabados, György; Bács, Zoltán; Ráthonyi, Gergely (Frontiers in Public Health, 2025)
COVID-19 has fundamentally altered the world, significantly affecting people’s health and quality of life. These changes may have impacted young adults’ physical activity (PA) and sedentary behavior (SB). This study aims to explore lifestyle changes among young adults, particularly focusing on the relationship between physical activity, sedentary behavior, and life satisfaction before and after the COVID-19 pandemic. To achieve this, we analyzed two surveys carried out in 2018 and 2024. A total of 799 participants were recruited for this age group, with 279 in 2018 and 520 in 2024. We employed T-tests, Pearson’s Chi-square tests, Mann–Whitney tests, and ordinal linear regression to uncover associations between physical activity and sitting time across the two periods, alongside various socio-demographic factors and predictors of life satisfaction. Our results reveal notable trends and changes in physical activity levels and sitting times among young adults in Hungary between 2018 and 2024. The most striking changes occurred in IPAQ (International Physical Activity Questionnaire) categorical scores, indicating a shift in activity levels across several demographic groups. The level of physical activity increased for both male and female respondents, residents of county seats and cities, as well as those living in relationships. In 2018, young Hungarian adults who maintained a balance of physical activity—including cycling, some home-based physical work, and limited sitting time—tended to report higher life satisfaction. In 2024, an interesting pattern emerged regarding leisure activities: individuals who engaged in very hard exercise during their free time reported varying levels of life satisfaction. Those who never engaged in very hard exercise or did so only once a week reported lower satisfaction compared to those who exercised daily. This finding aligns with existing research on the mental health benefits of regular intense physical activity. Furthermore, individuals whose physical activity was primarily work-related reported significantly lower life satisfaction compared to those whose physical activity was primarily leisure-related. This suggests that the context of physical activity is crucial in determining its impact on life satisfaction.